The Influence of Facial Injury during the First World War on the Development of Plastic and Reconstructive Surgery in Britain and Germany - Weiss, Lina; Monsch, Gian-Marco; Speth, Marlene; Saleh, Hesham (Facial Plastic Surgery, 2024)
In the First World War (WW1), different types of injuries became both political and economic factors for the main belligerent countries. This work illustrates the special role facial injuries played during and after the war and the profound impact they had on the field of Plastic Surgery in Britain and Germany.This is a historical work based on primary and secondary sources. English and German material was used to compile an overview of the development of Plastic and Reconstructive Surgery as a specialty during WW1 and up to the Second World War (WW2).Plastic and Reconstructive Surgery had the task of reconstructing male beauty and personalities, restoring the most intense, disfigured reminders of a terrible war in homes and the public. Looking at the significant role the specialty played during the war, remarkably, most of the contributors struggled to find financial support to develop designated specialized departments in the inter-war period. The specialty's connection to the emotional subject of facial disfigurement did not work in its favor at a time when people wanted to forget the horrors of the war.The developments in Britain and Germany during the WW1 were less isolated than often described and the inter-war period saw much effort for international collaboration. The different developments of WW2 further illustrate how essential the efforts of a strong group of individuals and support from authorities were for the evolution of Plastic Surgery as a specialty.
Keywords: facial reconstruction; war medicine; history of surgery